P496 Impact of ulcerative colitis on costs, work productivity and quality of life: a prospective study in a single referral centre. (25th January 2019) - Scrivo, B; Aiello, A F; Giuffrida, E; Calvaruso, V; Cappello, M
Abstract: Background: Ulcerative colitis (UC) is a chronic condition with a heavy economic burden for the health system and the society. Previous reports are available, but few data have been published in Italy, especially in the south. Methods: Our aim was to evaluate prospectively, in a 1-year period, the costs of UC in a consecutive cohort of Sicilian patients, and to assess their correlation with diseases activity (evaluated by Mayo Score), disease location, Work Productivity (WPAI-RCU) scoring and quality of life. Patients were asked to fill questionnaires on Quality of life (Eq5D), Cost of Illness (COI) and use of health resources (HRU). Data on demographic, hospitalisations, surgery, visits to the treating physician and to the emergency room, laboratory tests, radiological and endoscopic examinations, drugs. Results: We recruited 77 consecutive patients with UC coming to our IBD clinic from May 2017 to November 2017. At baseline mean age was 46.8 ± 13.6 years, 40 were males. Disease location was pancolitis in 31 patients. Twenty-four patients were in clinical remission, 24 had mild disease and 19 moderate activity. In 1-year observation period, mean cost/patient was €2898.8 for drugs, €3076.4 if we included the cost of diagnostic tests. Cost of drugs was higher in patients with pancolitis (€4142.6) than those with a limited disease (2599.7 €) and proctosigmoiditis (€2112.9) (p = 0.004). A relationship was also observed between drug therapy and disease activity (p <0.05). There was a statistical difference among patients on biologics (€6395.5), when compared with thiopurines (€368.7) and other conventional treatments (€554.6) (p <0.001). Disease activity was significantly related with work productivity (p = 0.05) and quality of life (p <0.001). Conclusions: Our preliminary results confirm that in Southern Italy, UC has high direct costs mainly related to drug therapies and in particular to biological therapy. Mean cost/patient/year is €3076.4 and it is significantly associated with disease activity and extent of disease. Disease activity impacts significantly on work productivity and quality of life. These preliminary results will provide useful information to health authorities to guide resource allocation and physicians to improve disease management.